Fluid Administration in Emergency Room Limited by Lung Ultrasound in Patients with Sepsis: Protocol for a Prospective Phase II Multicenter Randomized Controlled Trial - Mohamed, Mouhand F H; Malewicz, Nathalie M; Zehry, Hanan Ibrahim; Hussain, Dina A Monim; Barouh, Judah Leão; Cançado, Adriana V; Silva, Jeancarllo Sousa; Suwileh, Salah; Carvajal, Jose Retamal (JMIR Research Protocols, 2020)
BackgroundSepsis remains a major health challenge with high mortality. Adequate volume administration is fundamental for a successful outcome. However, individual fluid needs differ between patients due to varying degrees of systemic vasodilation, circulatory flow maldistribution, and increased vascular permeability. The current fluid resuscitation practice has been questioned. Fluid overload is associated with higher mortality in sepsis. A sign of fluid overload is extravascular lung water, seen as B lines in lung ultrasound. B lines correlate inversely with oxygenation (measured by a ratio of the partial pressure of arterial oxygen to the fraction of inspired oxygen ie, PaO2/FiO2). Thus, B lines seen by bedside ultrasound may have a role in guiding fluid therapy. ObjectiveWe aim to evaluate if fluid administration guided by lung ultrasound in patients with sepsis in emergency departments will lead to better oxygenation and patient outcomes than those in the standard therapy. MethodsA phase II, multicenter, randomized, open-label, parallel-group, superiority trial will be performed. Patients will be recruited at emergency departments of the participating centers. A total of 340 patients will be randomly allocated to the intervention or standard-of-care group (30mL/kg). The intervention group will receive ultrasound-guided intravenous fluid until 3 B lines appear. The primary outcome will be oxygenation (measured as PaO2/FiO2 ratio) at 48 hours after starting intravenous fluid administration. Secondary outcomes will be patients’ outcome parameters, including oxygenation after 15 mL/kg fluid at 6, 12, 24, and 48 hours; sepsis progress through Sequential Organ Failure Assessment (SOFA) scores; pulmonary edema evaluation; and 30-day mortality. ResultsThe trial will be conducted in accordance with the Declaration of Helsinki. Institutional review board approval will be sought after the participating sites are selected. The protocol will be registered once the institutional review board approval is granted. The trial duration is expected to be 1.5-2.5 years. The study is planned to be performed from 2021 to 2022, with enrollment starting in 2021. First results are expected in 2022. Informed written consent will be obtained before the patient’s enrollment in the study. An interim analysis and data monitoring will ensure the patient safety. The results will be published in a peer-reviewed journal and discussed at international conferences. ConclusionsThis is a protocol for a randomized control trial that aims to evaluate the role of bedside ultrasound in guiding fluid therapy in patients with sepsis via B lines evaluation. International Registered Report Identifier (IRRID)PRR1-10.2196/15997